A crítica da religião no século XIX: Feuerbach, Marx, Nietzsche e Freud - Verlig, Fabiano (Revista eclesiástica brasileira, 2018)
In this article we will try to contextualize the debate about religion, exposing the ideas of the main authors who influenced the critique of religion in the nineteenth century such as Feuerbach, Marx, Nietzsche and Freud. It will be tried to show that these authors have something in common that the philosophy of the later religion seeks to surpass. All these philosophers deal in one way or another with the question of the “death of God.” They announce and confirm this fact. Beginning with Feuerbach and culminating in Freud, God is banished as a possible reality. If God is banished, the religion that speaks of this God must also be banished and something else must be put in its place. However, this is not what happens. The “death of God” is understood as “eclipse of God” and instead of the emptiness that his death would leave, a new way of thinking in God emerges. The purpose of this article is to contextualize what has been called the “death of God” and to show that what happened in reality was an “eclipse of God.” In this context, the thought of Rubem Alves is interesting to think religion beyond The article aims to help understand this movement of the nineteenth century on religion and contextualize the debate that Rubem Alves brings from his work without us, however in a detailed analysis of the Alvesian thought.